PENGARUH KINERJA KEUANGAN TERHADAP TINGKAT BAGI HASIL SIMPANAN MUDHARABAH BANK SYARIAH : SURVEI PADA BANK MUAMALAT INDONESIA TBK - Kiagus Andi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
The objective of this research is to know financial performance the relationship Bank syariah to deposit sharing holder level of mudharabah by using Bank Muamalat Indonesia as research object. Other objective is as one of the study medium banking of Bank Syariah specially and Syariah economics in general.The test in this research uses deposit sharing holder level of mudharabah as dependent variable and financial ratio those are ROA, ROE, FDR, GWM, BOPO, NIM and CAR as its variable. This ratios is as financial ratio which used consistently by Bureau Research of Infobank in assessing and rating banking of national. Data which is used in this research is annual financial statement of publication of PT Bank Muamalat Indonesia Tbk for year 1999-2003 which made no difference in intropolation data.By using analyzer of SPSS 11.0 for windows model multiple linear regression, equation of new regression get away classic assumption test if ROE variable and of GWM released from equation because the happening of multicolinerity. Result of this test can be concluded that 90.1% variance of variable amount Sharing Holder can be explained by variance from is tyhe fifth of independent variable, while 9.9% other explained by other variable outside that used model. Then, assess of constant © 16.556 with significant level 0.000 indicating that there is free variable which included into model and individually that have influenced of significant in explaining variable of Sharing Holder.F-Test conducted, that has proved that significant level is 0.000 the fifth of independent variable by together have correlation which are positive and significant toward deposit sharing holder level of mudharabah. But F-Test by parsial show only BOPO variable and NIM owning positive correlation and significant toward deposit sharing holder level of mudharabah with R each 0.55 and 0.616, while ROA, FDR variable, and CAR do not significant to deposit sharing holder level of mudharabah with value of significant each 0.950, 0.300, and 0.179.